The Impact of Unified Payments Interface on Enhancing Financial Inclusion in Rural Tamil Nadu - C. Muthukumar; C. Paramasivan (Academic Bright Collaboration, 2026)
The rapid growth of digital financial technologies has transformed financial service delivery in developing economies such as India. However, limited empirical evidence exists on how Unified Payments Interface (UPI) usage relates to measurable financial inclusion outcomes in rural areas. This study aims to examine the association between UPI usage and financial inclusion in rural Tamil Nadu. The study is based on primary data collected from 320 respondents using a structured questionnaire and convenience sampling. Financial inclusion was measured using a composite index constructed from indicators such as access to banking services, frequency of digital transactions, and usage of formal financial instruments. Descriptive statistics, chi-square tests, and one-way ANOVA were employed for data analysis. The findings indicate that UPI is widely used for transactions such as money transfers and bill payments, with users reporting high satisfaction levels. The results further show a significant association between education level and UPI usage frequency, while financial inclusion scores differ across income groups. However, these findings indicate associations rather than causal relationships. Key barriers to UPI usage include limited internet access, low awareness, and security concerns. The study suggests that UPI usage is positively associated with financial inclusion indicators in rural areas. However, the results are subject to limitations due to the use of convenience sampling, which restricts generalizability.